Influence of CaCO₃ in glass fibre/unsaturated polyester composite on thermal and flexural creep behaviour - Johari, Ahmad Nazrin (2019)
The main objective of this experimental study is to investigate the influence of applying Calcium Carbonate (CaCO₃) on the flexural creep behavior of the coupon sample and to predict the service life of the composite samples. One of the test was short-term testing. Flexural test jig has been used along with furnace chamber HK160 for samples tested with different temperatures until it fails while the Long-term test has been done using constant temperature of 30°C. Master curve generated through the Time-temperature Superposition Principle via TRIOS software purposely done to predict the longevity of the sample. The patterns of the failure through conventional method shown consistent increment of temperature for short term test inside furnace until it reached 120°C, the sample for UPE with fiber-glass (without presence of CaCO₃) fails and fracture. For long term test results of creep in room temperature set up to be consistent at (30°C). The results shown small deformation on the center for both of the specimen (with CaCO₃ and without CaCO₃) with respect to time for 45 days of testing. Master curve produced displayed different results for UPE samples (with the presence of CaCO₃) for 95°C and 160°C respectively. The longevity of the sample of coupon test which can reach up to 25 years of services for long-term (conventional testing) under consistent room temperature (30°C). Using master curve method for TTS, results were at consistent form (without failure) for both UPE coupon sample (with and without CaCO₃ reinforced) at 30°C but fractured at 120°C for coupon sample (without CaCO₃), and TTS master-curve prediction for temperature 95°C fails on the 111th Day while for temperature 160°C, it fails on the 11th Day. Therefore, the use of CaCO₃ shows significant benefits to the longevity of UPE coupon samples rather than absence of CaCO₃ in the samples.